Evaluation of Priority Pathways in the Stages of Acceptance for the Resilient Youth Scholarship in Surabaya City - Fadhilazza, Sheikha; Rejasa , Dana; Risaldi, Muhammad; Pertiwi, Vidya Imanuari (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract The Surabaya City Resilient Youth Scholarship Program is a strategic initiative of the Surabaya City Government in supporting the equalization of higher education for economically disadvantaged people in the orphan category. This study aims to evaluate the priority pathways in the scholarship acceptance stages using a qualitative descriptive approach. Based on William Dunn's policy evaluation theory, six main indicators, namely effectiveness, efficiency, adequacy, equity, responsiveness, and feasibility, are used as the basis for analysis. The results of the study indicate that this program has been able to reach students from orphan and poor family backgrounds in a targeted manner, there are still obstacles in the form of limited quotas and strict tiered selection and high academic requirements. The Surabaya City Government has demonstrated responsiveness through the provision of a digital information platform (BeSmart) and a needs-based field survey. Continuous evaluation and improvement efforts are still needed so that this program can provide broader and more equitable benefits for Surabaya residents. Keywords: Resilient Youth Scholarship, Policy Evaluation, Higher Education, Education Equity, Surabaya City